Improving Self-Care Behavior of Elderly Group with Diabetes Mellitus through Diabetes Self Management Intervention - Naralia, Widya; Diorarta, Raphita; Fadhani, Masyithah; Sahar, Junaiti (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: The elderly are one of the age groups that are easily affected by diabetes mellitus due to the decline in organ function and unhealthy lifestyles. Self-care management of diabetes is crucial for helping to control the blood glucose levels of individuals with diabetes mellitus. Self-care management can be carried out through education, discussions, and the practice of physical exercise to regulate blood glucose levels. The implementation of self-care management interventions is considered effective when conducted in groups among the elderly.Purpose: This research aims to observe changes in the knowledge and attitudes of the elderly, as well as changes in their independence skills.Methods: The implementation of the Diabetes Self-Management intervention was carried out on 33 elderly individuals with diabetes who were organized into one group. The intervention was conducted over 12-14 weeks, which included education, simulation, and chair-based exercise (CBE) training performed once a week consecutively.. This research uses a pre-post group design with t-test analysis to determine changes in the self-care behavior of group members.Results: There was an increase in the average score of 1.54 in the knowledge domain, and an average score of 5.18 in the attitude domain. Additionally, there was a decrease in the average blood glucose level of 61.61 mg/dL in the elderly group with diabetes mellitus. Other improvements were also observed in the changes in the Functional Independence variables for motoric and cognitive functions.Conclusion: Diabetes self-management intervention has become one of the effective strategies that can be implemented in elderly groups with diabetes in the community.